The impact of exclusion of the urban ultra-poor from public housing on the lives of those excluded - Ndjembela, Toivo Djeiko (Graduate School of Development Policy and Practice, 2020)
Namibia has experienced an upward growth of informal settlements since independence. Such settlements have become an integral part of urban areas in the country, a situation that begs for, first, acceptance of this reality and, second, action to mitigate challenges that are generally associated with living in such areas. Due to such challenges, which include high rates of poverty as a result unemployment among slum dwellers, informal settlements have become the glaring face of social exclusion in Namibia. In order to arrest this exclusion, planners and policymakers need to find ways of upgrading these settlements so that the residents’ quality of life is incrementally enhanced. This paper is an outcome of a study conducted in five informal settlements in Windhoek, with a deliberate focus on access - or lack thereof - to basic services and infrastructure. Having highlighted the level of exclusion in those informal areas, this paper recommends that instead of re-inventing the wheel, government must embark of a sustained deliberate exercise to upgrade the existing informal settlements instead of demolishing or eradicating them. Policymakers are urged in this study to accept that people, out of desperation fed by social factors, would continue to occupy land illegally. Policymakers must thus find ways to amicably regulate these invasions. This would help attain a degree of inclusivity and compliance with the Constitutional requirement of ensuring dignity for everyone in the country.